GROTESQUE COMPONENTS IN CHARLES DICKENS’ TO BE TAKEN WITH A GRAIN OF SALT AND MARY ELIZABETH BRADDON’S EVELINE’S VISITANT - Hajo, Suhair Fuaad (Universitas Islam Sumatera Utara (UISU), 2023)
This paper attempts to define the grotesque and its primary literary features before examining the grotesque components in two Victorian authors' works with the goal of separating their approaches to the grotesque based on gender. The most well-known novelist of the Victorian era, Charles Dickens will be one of the authors covered in this paper through his story To be Taken with a Grain of Salt, and the other one is Mary Elizabeth Braddon’s story Eveline’s Visitant. Dickens and Braddon particularly make use of the grotesque elements to convey their ideas and ideals through satire, comedy, tragedy, suspense, and a sense of fear, gloom, and obscurity. The research results show that both tales can be regarded as significant Victorian grotesque literature since they share, in various ways, elements of the grotesque notion. The real meaning of the grotesque is only exposed by itself-contradictory nature with the opposite, which is in this sense the ideal. Both stories are based on the main contrast between the spiritual and material worlds. They attempt to persuade us that there is yet another mysterious force that, despite the efforts to conceal it in the physical world, it exposes human wrongdoing. Thus, abnormal human beings, ghostly figures, and terrifying events will be detected through which grotesque elements are found.